The Role Of Incentives In Improving Work Performance During The Reconstruction Phase "Field study on the Baniyas refinery" - فياض , لينا (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aimed to determine the role of incentives in improving the work performance of the Banias Refinery, by defining the role of incentives represented (job stability, employee involvement, rewards) in improving the work performance of the Banias Refinery, the researcher relied on the deductive approach as a method of thinking, and on the descriptive approach a procedural approach To find out the availability of incentive dimensions at Baniyas refinery. Where the researcher distributed a questionnaire to 350 workers, the study concluded that the lowest mean of the responses of the sample members to the phrases that measure the delegated participation of decision-making workers is 2.43, which is less than the mean of neutrality 3, and moral, meaning that workers do not participate in the discussion of any decision The company issues it according to the answers of the sample members. At lower levels, this affects their performance which is reflected in the performance of the work.